Pharmacotherapics Advice in Guidelines for COVID-19 - Chen, Zhang-Ren; Zhou, Ying; Liu, Jin; Peng, Hong-Wei; Zhou, Jian; Zhong, Hai-Li; Liu, Li-Li; Lai, Ming-Fang; Wei, Xiao-Hua; Wen, Jin-Hua (Frontiers in Pharmacology, 2020)
Since December 2019 to May 2020, coronavirus disease 2019 (COVID-19) has infected over 6 million people worldwide. Due to the sudden and rapid outbreak, the effective treatment of COVID-19 is scarce. Based on the national clinical trials of novel treatments, China, Italy, Germany, and other countries and organizations have published multiple guidelines for COVID-19 and advised many medicines, such as chloroquine, and tocilizumab. In this paper, we summarized the pharmacotherapy of those guidelines for COVID-19, highlighted the updates of the pharmacotherapy of those guidelines, and reviewed the efficacy and safety of those anti-COVID-19 drugs.